Sexuality education among neglected adolescents: the case of out-of-school female house-helps (2012)
Adolescent sexuality constitutes one of the most unattended aspects of young people's development in Nigeria. Consequently, reproductive health mishaps such as sexually transmitted infections, unplanned pregnancies, abortion, maternal morbidity and mortality are common features among different categories of women. This study which anchored on Social Action and Rational Choice Theories investigated sexuality education among out-school female adolescent house-helps in Ibadan as a way of understanding the culture of silence that characterises young people's sexual orientation. Data were collected through 1020 questionnaires administered on employers of house-helps selected through a multi-stage sampling technique. Indepth Interviews were conducted among 27 respondents - 21 house-helps and 6 house-help employers. In addition, 2 case studies were undertaken among househelps. Findings reveal that although a large majority of adolescents do not receive sex education from parents and guardians, house-helps are disproportionately more disadvantaged. Some house-helps are given sexuality education not primarily for their personal benefit but as a means to indirectly educate guardians' biological children since these employers' comfort levels are low to personally do that. Prioritising sexuality education among adolescents and house-helps in particular can go a long way in demystifying unnecessary insensitivity that pervades sexuality discourses among Nigerian youths.